Eco-Efficiency in the National Registry of Identification and Civil Status – RENIEC, autonomous entity of the Peruvian State - Barreto Dávila, Celso Nicanor (2022)
Eco-efficiency Management at RENIEC, where its 4 000 servers nationwide use and consume huge amounts of resources for their processes, which constitutes an environmental problem due to the generation of negative impacts. Through this research with a scientific approach, and methodology of experimental design and analysis of variance applied to a random sample of servers, forming two groups (experimental and control), who underwent a pre and posttest (both groups), and in turn, the experimental group was intensively trained in eco-efficiency and related topics. Likewise, reports of purchases and monthly consumption of the entity were analyzed; achieving the change of paradigms and better performance of the servers, such as: efficient and rational use of resources (electricity, water, paper, toner, fuel and others), green purchases and eco-design. The results obtained were the saving of institutional spending, reduction of negative environmental impacts and the inflection of consumption indicators such as: Water in 0.17%, electricity in 31%, bond paper in 80.9%, toner in 25% and waste generation. solids at 19%; evidencing eco-efficient practices of the servers in their processes.